2012
DOI: 10.1614/wt-d-11-00071.1
|View full text |Cite
|
Sign up to set email alerts
|

Sulfentrazone and Carfentrazone Accelerate Broadleaf Weed Control with Metsulfuron

Abstract: Ground ivy and khakiweed are troublesome broadleaf weeds of warm-season turfgrass. Field studies were conducted in Tennessee (TN) and Texas (TX) from 2008 to 2010 to evaluate the efficacy of sulfentrazone plus metsulfuron and carfentrazone plus metsulfuron tank mixtures compared with metsulfuron alone for control of ground ivy and khakiweed. In TN, sulfentrazone plus metsulfuron and carfentrazone plus metsulfuron provided accelerated control of ground ivy compared with metsulfuron alone. Over a 2-yr period, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Decreasing temperatures in late October and early November may have reduced the activity of metsulfuron compared with other herbicides; this treatment ultimately provided 91% control when evaluated in spring (Table 3). In colder temperatures, sulfonylurea herbicides like metsulfuron are less likely to inhibit the production of amino acids within the target plant; as a result, herbicide efficacy is generally reduced, and symptomology is slow to develop (Brosnan et al, 2012; Hutto et al, 2008; Willis, 2008). Despite differences in control in Environment 1, there were no differences in ground ivy control among herbicides for Environments 2 and 3 when rated 4 wk after application in November (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing temperatures in late October and early November may have reduced the activity of metsulfuron compared with other herbicides; this treatment ultimately provided 91% control when evaluated in spring (Table 3). In colder temperatures, sulfonylurea herbicides like metsulfuron are less likely to inhibit the production of amino acids within the target plant; as a result, herbicide efficacy is generally reduced, and symptomology is slow to develop (Brosnan et al, 2012; Hutto et al, 2008; Willis, 2008). Despite differences in control in Environment 1, there were no differences in ground ivy control among herbicides for Environments 2 and 3 when rated 4 wk after application in November (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Ground ivy control improved when 2,4‐D and triclopyr were tank‐mixed with other herbicides or with each other (Olson and Wright, 1988; Vrabel, 1987). More recent research found that aminocyclopyrachlor and metsulfuron applied alone or in tank mixtures with sulfentrazone or carfentrazone can control ground ivy (Beck et al, 2014; Brosnan et al, 2012). Ground ivy control from quinclorac is variable in the literature and may be dependent on the population (Calhoun and Baird, 1999; Czarnota et al, 2001, Kohler et al, 2004b; Neal and Senesac, 1991).…”
mentioning
confidence: 99%
“…Fluroxypyr provides adequate control of ground ivy in cool‐season turf, but the observed control was less effective and less consistent compared with applications of triclopyr (Kohler et al, 2004b; Reicher and Weisenberger, 2007). More recent research also indicates that aminocyclopyrachlor (Patton et al, 2013b) and metsulfuron applied alone or tank‐mixed with other herbicides (Brosnan et al, 2012) effectively control ground ivy.…”
mentioning
confidence: 99%
“…However, turf managers are limited to granular formulations of oxadiazon after greenup because of excessive injury caused by sprayable formulations (Johnson 1976;Johnson and Carrow 1999;. Sulfentrazone is another Protox inhibitor that is applied PRE or POST for control of sedges, broadleaf weeds, and select grassy weeds in warm-and cool-season turfgrasses (Blum et al 2000;Brecke et al 2005;Brosnan et al 2012a;McCullough et al 2012b). Carfentrazone is a POST herbicide that is used for controlling mosses and broadleaf weeds, and is generally safe on all major warm-and cool-season turfgrasses (Senseman 2007;Yelverton 2005).…”
mentioning
confidence: 99%